Acute Spontaneously Resolving Pulmonary Vasculitis: A Case Report - James B. Geake; Graeme Maguire (Case Reports in Immunology)
This is the first description that we are aware of describing the spontaneous resolution of an acute pulmonary vasculitis, possibly secondary to microscopic polyangiitis. Haemoptysis is a common symptom for patients presenting to primary and tertiary referral centres, and pulmonary vasculitis is one of a variety of aetiologies that should always be considered. The pulmonary vasculitides are difficult diagnostic and management problems. They are encumbered by a relative paucity of level 1 evidence addressing their diagnosis, classification, and treatment. This is therefore an important paper to publish because it adds to the global breadth of experience with this important clinical condition.